Implementation of Pancasila Values Against the Prevention of Radicalism Movement in the Digital Age - Walid, Hafidz Muhammad Dzidan (Indonesian Journal of Counter Terrorism and National Security, 2022)
Indonesia is a country that has extraordinary diversity, from culture to religion. Indonesia has a state basis, namely Pancasila, where every item of Pancasila has a meaning or content that must be understood by every citizen. Every Indonesian citizen is obliged to choose one religion that he adheres to. Indonesia has six religions that are mutually tolerant. However, there are some people who do not understand Pancasila so that radical movements appear. The purpose of this study is to examine the important role of Pancasila in society and to analyze the importance of understanding Pancasila values ​​in everyday life for the sake of creating tolerance among others. While this research method is a qualitative descriptive research method. The results of this study in this digital era, Indonesian people will understand the importance of Pancasila values ​​as the basis of the state that must be implemented in everyday life. Indonesian people will also have a high sense of tolerance among others and uphold the motto of Bhinneka Tunggal Ika. So that Indonesia will become a harmonious religious country without any elements of war from within, let alone religious social movements that smell elements of radicalism.